Lamivudine prophylaxis prevents hepatitis B virus reactivation in anti-HBc positive patients under rituximab for non-Hodgkin lymphoma. Issue 3 (March 2019) - Loglio, Alessandro; Viganò, Mauro; Grossi, Glenda; Labanca, Sara; Goldaniga, Maria; Pompa, Alessandra; Farina, Lucia; Rumi, Mariagrazia; Corradini, Paolo; Facchetti, Floriana; Lunghi, Giovanna; Baldini, Luca; et al.
Abstract: Backgound: A significant proportion of hepatitis B surface antigen (HBsAg) negative/anti-hepatitis B core antigen (anti-HBc) positive patients with non-Hodgkin lymphoma (NHL) undergoing rituximab-based chemotherapy (R-CT) may suffer hepatitis B virus (HBV) reactivation. Aims: We wanted to assess efficacy and safety of lamivudine (LMV) prophylaxis to prevent this complication. Methods: Eighty-five consecutive HBsAg negative/anti-HBc positive NHL patients (71 years, 100% serum HBV DNA undetectable, 74% anti-HBs positive) received LMV coadministered with R-CT and for 18 months after the end of R-CT. Serum ALT, HBsAg, anti-HBs and HBV DNA were assessed every 4 months during and after end of LMV. Results: During 39 (2–108) months of study period, including 21 months of LMV and 27 additional months after LMV discontinuation, one patient (2%) had HBV reactivation, 31 months after stopping LMV and during administration of new immunosuppressive regimens, without LMV prophylaxis, owing to incomplete oncological response. A 50% decline of anti-HBs titers occurred in 22/63 (35%) patients, including 12 who became anti-HBs seronegative. Five (6%) patients had ALT increase during R-CT but none required R-CT discontinuation. Seventeen (20%) patients died, all for tumour progression. Conclusion: LMV prophylaxis is safe and effective in preventing HBV reactivation in HBsAg negative/anti-HBc positive NHL patients receiving R-CT.